ROAD AS IMAGERY COMPONENT OF "LIFE" CONCEPT IN "MY LIFE" BY A.P. CHEKHOV (Proceedings of Southern Federal University. Philology, 2013)
N.M.ScharenskayaKeywords: Chekhov, concept, life, road.The article is devoted to the study of road as an important component of "life" concept in A.P. Chekhov’s "My Life". Treatment of the image by different characters is analyzed, text details relating to the concept are considered, it is proved that words and object-element content of the text is shaped by the imagery of road as a way of life.